Effects of channel structure consisting of ZnO/Al2O3 multilayers on thin-film transistors fabricated by atomic layer deposition. (1st March 2017) - Cui, Guodong; Han, Dedong; Dong, Junchen; Cong, Yingying; Zhang, Xiaomi; Li, Huijin; Yu, Wen; Zhang, Shengdong; Zhang, Xing; Wang, Yi
Abstract: By applying a novel active layer comprising ZnO/Al2 O3 multilayers, we have successfully fabricated fully transparent high-performance thin-film transistors (TFTs) with a bottom gate structure by atomic layer deposition (ALD) at low temperature. The effects of various ZnO/Al2 O3 multilayers were studied to improve the morphological and electrical properties of the devices. We found that the ZnO/Al2 O3 multilayers have a significant impact on the performance of the TFTs, and that the TFTs with the ZnO/15-cycle Al2 O3 /ZnO structure exhibit superior performance with a low threshold voltage ( V TH ) of 0.9 V, a high saturation mobility (μsat ) of 145 cm 2 V −1 s −1, a steep subthreshold swing (SS) of 162 mV/decade, and a high I on / I off ratio of 3.15 × 10 8 . The enhanced electrical properties were explained by the improved crystalline nature of the channel layer and the passivation effect of the Al2 O3 layer.